2021
DOI: 10.1093/jas/skab035
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting performance response of pigs exposed to different challenge models: a multivariate approach

Abstract: Factors associated with the severity with which different challenge models (CMs) compromise growth performance in pigs were investigated using hierarchical clustering on principal components (HCPC) analysis. One hundred seventy-eight studies reporting growth performance variables (average daily gain [ADG], average daily feed intake [ADFI], gain:feed [GF], and final body weight [FBW]) of a Control (Ct) vs. a Challenged (Ch) group of pigs using different CMs (enteric [ENT], environmental [ENV], lipopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…The growth performance response of pigs to respiratory pathogens will be dependent on the agent involved. Two recent meta-analyses showed similar results related to severity of respiratory challenge [ 8 , 9 ]. In general, respiratory diseases were less detrimental to performance than the other immune challenges, which may possibly be due to a greater degree of compensatory growth following respiratory infections [ 77 ].…”
Section: Immune Challenges In Pork Productionmentioning
confidence: 64%
See 4 more Smart Citations
“…The growth performance response of pigs to respiratory pathogens will be dependent on the agent involved. Two recent meta-analyses showed similar results related to severity of respiratory challenge [ 8 , 9 ]. In general, respiratory diseases were less detrimental to performance than the other immune challenges, which may possibly be due to a greater degree of compensatory growth following respiratory infections [ 77 ].…”
Section: Immune Challenges In Pork Productionmentioning
confidence: 64%
“…While both feed intake and nutrient utilization efficiency influence pig performance, the extent to which reductions in these factors are related to the reduction in performance is dependent on the specific immune challenge [ 8 ]. For example, Rodrigues et al [ 9 ] showed that the reduction in growth in challenged compared with control pigs associated with a reduction in feed intake was 14, 4, 45, 1, and 1% in pigs challenged with enteric pathogens, environmental stressors, bacterial lipopolysaccharide (LPS), respiratory pathogens, and sanitary conditions, respectively. This is important to note as, in experimental environments, several challenge models are used to investigate stimulation of the immune system and the associated effects on outcomes such as growth performance impairment, nutrient requirements, and immune status.…”
Section: Immune System Stimulation Nutrient Efficiency and Requirementsmentioning
confidence: 99%
See 3 more Smart Citations